University students' self-efficacy, attitudes, and intentions toward chemistry: Myanmar context - Mya Thet Mon (Journal of Green Learning, 2022)
This research examined the self-efficacy beliefs, attitudes towards Chemistry, and intentions to take future Chemistry courses in a sample of (n = 112) students from selected universities in Myanmar. The main purpose of the study was to determine the university students' self-efficacy, attitudes, and intentions toward Chemistry in Myanmar context. Findings indicate that self-efficacy (Mean=2.05) and attitude (Mean=2.47) are both significant, making a larger unique contribution. According to the findings, Self-efficacy of undergraduate students was slightly significant indicating confidence of the participants. Our findings suggest that in general, although the population at Myanmar universities slightly feel confident in their ability to perform in Chemistry (Mean=2.06, SD=0.60), have strong attitude towards Chemistry (Mean=2.47, SD=0.84), and moderate intentions toward enrolling in future Chemistry courses (M=1.98, SD=0.97). In the current context, the students believe that they are capable of successfully performing tasks affiliated with Chemistry content. Students with a high self-efficacy toward Chemistry will be more likely to take on the challenge of Chemistry and persist through the courses. Finally, implications for educators and administrators are discussed.